The proline-rich homeodomain (PRH/HEX) protein is down-regulated in liver during infection with lymphocytic choriomeningitis virus (2005)
ABSTRACT: The proline-rich homeodomain protein, PRH/HEX, participates in the early development of the brain, thyroid, and liver and in the later regenerative processes of damaged liver, vascular endothelial, and hematopoietic cells. A virulent strain of lymphocytic choriomeningitis virus (LCMV-WE) that destroys hematopoietic, vascular, and liver functions also alters the transcription and subcellular localization of PRH. A related virus (LCMV-ARM) that does not cause disease in primates can infect cells without affecting PRH. Biochemical experiments demonstrated the occurrence of binding between the viral RING protein (Z) and PRH, and genetic experiments mapped the PRH-suppressing phenotype to the large (L) segment of the viral genome, which encodes the Z and polymerase genes. The Z protein is clearly involved with PRH, but other viral determinants are needed to relocate PRH and to promote disease. By down-regulating PRH, the arenavirus is able to eliminate the antiproliferative effects of PRH and to promote liver cell division. The interaction of an arenavirus with a homeodomain protein suggests a mechanism for viral teratogenic effects and for the tissue-specific manifestations of arenavirus disease.